2017
DOI: 10.2298/fil1701125s
|View full text |Cite
|
Sign up to set email alerts
|

A family of the incomplete hypergeometric functions and associated integral transform and fractional derivative formulas

Abstract: Recently, Srivastava et al. [Integral Transforms Spec. Funct. 23 (2012), 659-683] introduced the incomplete Pochhammer symbols that led to a natural generalization and decomposition of a class of hypergeometric and other related functions as well as to certain potentially useful closed-form representations of definite and improper integrals of various special functions of applied mathematics and mathematical physics. In the present paper, our aim is to establish several formulas involving integral transforms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For various investigations involving the Hadamard product (or the convolution), the interested reader may refer to recent papers on the subject (see, for example, [68,69] and the references cited therein). Also we require the Fox-Wright function p q (z) (p, q ∈ N 0 ) with p numerator and q denominator parameters defined for a 1 , .…”
Section: Mathieu Series and Its Generalizationsmentioning
confidence: 99%
“…For various investigations involving the Hadamard product (or the convolution), the interested reader may refer to recent papers on the subject (see, for example, [68,69] and the references cited therein). Also we require the Fox-Wright function p q (z) (p, q ∈ N 0 ) with p numerator and q denominator parameters defined for a 1 , .…”
Section: Mathieu Series and Its Generalizationsmentioning
confidence: 99%
“…Recently, Agarwal et al [25] found the solution of non-homogeneous time fractional heat equation and fractional Volterra integral equation using integral transform of pathway type. Also, Srivastava et al [26] and [27] found some results involving generalized hypergeometric function and generalized incomplete gamma function by using P δ -transform.…”
Section: Introductionmentioning
confidence: 99%
“…For various other investigations involving the Hadamard product (or the convolution), the interested reader may be referred to several recent papers on the subject (see, for example, [27,28] and the references cited in each of these papers).…”
Section: Introductionmentioning
confidence: 99%